(untitled) (Revista de Psicología, 2024)
Introduction. In Latin America, studies of cognitive plasticity in aging are scarce. The AVLT-LP is a modified version of the Rey’s List that assesses cognitive plasticity by assessing learning potential. There are no normative data for the AVLT-LP for older adults. Objective. To study the connections between sociodemographic variables (sex, age, and educational level) and the AVLT-LP in older people, to present local reference values ​​of the AVLT-LP. Methodology. The sample consisted of 107 older adults between 60 and 89 years of age from Buenos Aires. The correlation and differences of variables of the AVLT-LP were analyzed according to sex, age, and educational level. Results. A statistically significant negative correlation was demonstrated between age and AVLT-LP, and differences were observed according to sex. There was no correlation between the variables of the AVLT-LP and the years of education. Conclusions. The AVLT-LP presents differences according to age and sex but did not present correlation with the years of formal education, thus resulting in a useful tool to describe episodic memory functioning in healthy older people with different educational levels. Therefore, these variables were considered to present the reference values ​​of the AVLT-LP for older adults from Buenos Aires.